Managing the incidence of selective reporting bias: a survey of Cochrane review groups - Reid, Emma K; Tejani, Aaron M; Huan, Lawrence N; Egan, Gregory; O’Sullivan, Cait; Mayhew, Alain D; Kabir, Monisha (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Selective reporting bias (SRB), the incomplete publication of outcomes measured or of analyses performed in a study, may lead to the over- or underestimation of treatment effects or harms. Cochrane systematic reviews of interventions are required to assess the risk of SRB, achieved in part by applying the Cochrane risk of bias tool to each included randomised trial. The Cochrane Handbook outlines strategies for a comprehensive risk of bias assessment, but the extent to which these are followed by Cochrane review groups (CRGs) has not been assessed to date. The objective of this study was to determine the methods which CRGs require of their authors to address SRB within systematic reviews, and how SRB risk assessments are verified. Methods A cross-sectional survey was developed and distributed electronically to the 52 CRGs involved in intervention reviews. Results Responses from 42 CRGs show that the majority refer their authors to the Cochrane Handbook for specific instruction regarding assessments of SRB. The handbook strategies remain variably enforced, with 57 % (24/42) of CRGs not requiring review authors to search for included trial protocols and 31 % (13/42) not requiring that contact with individual study authors be attempted. Only half (48 %, 20/42) of the groups consistently verify review authors’ assessments of the risk of SRB to ensure completeness. Conclusions A range of practices are used by CRGs for addressing SRB, with many steps outlined in the Cochrane Handbook being encouraged but not required. The majority of CRGs do not consider their review authors to be sufficiently competent to assess for SRB, yet risk of bias assessments are not always verified by editors before publication. The implications of SRB may not be fully appreciated by all CRGs, and resolving the identified issues may require an approach targeting several steps in the systematic review process.